2015
DOI: 10.1016/j.jgr.2015.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis rates, growth, and ginsenoside contents of 2-yr-old Panax ginseng grown at different light transmission rates in a greenhouse

Abstract: BackgroundGinseng is a semishade perennial plant cultivated in sloping, sun-shaded areas in Korea. Recently, owing to air-environmental stress and various fungal diseases, greenhouse cultivation has been suggested as an alternative. However, the optimal light transmission rate (LTR) in the greenhouse has not been established.MethodsThe effect of LTR on photosynthesis rate, growth, and ginsenoside content of ginseng was examined by growing ginseng at the greenhouse under 6%, 9%, 13%, and 17% of LTR.ResultsThe l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…The ginsenoside content of ginseng roots increased as the light transmission rate (LTR) increased. A study of 2-year-old ginseng reported that the total ginsenoside content of ginseng grown at 17% LTR was 49.7% and 68.3% higher than ginseng grown at 6% LTR in August and at final harvest, respectively [38]. These results are consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 92%
“…The ginsenoside content of ginseng roots increased as the light transmission rate (LTR) increased. A study of 2-year-old ginseng reported that the total ginsenoside content of ginseng grown at 17% LTR was 49.7% and 68.3% higher than ginseng grown at 6% LTR in August and at final harvest, respectively [38]. These results are consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 92%
“…P . ginseng seedling roots randomly collected from 1 m 2 of each plot under different treatments were dried to calculate yields [33]. Data reflect the mean of triplicates.…”
Section: Methodsmentioning
confidence: 99%
“…The total leaf area per petiole in 'Kowon' (202.4 cm 2 ) was higher than the two control cultivars (Table 1). Many studies have reported that photosynthesis is higher in ginseng with a larger leaf area, which ultimately increases the size of the root (Parmenter and Littlejohn, 2000;Hughes and Proctor, 1981;Jang et al, 2015), and the same is expected in 'Kowon'. The results of the below-ground characteristics of 'Kowon' are presented in Table 2.…”
Section: Growth Characteristics Of the Above-and Below-ground Partsmentioning
confidence: 80%